A Focus On The Psychological Well-being Of Muslim Religious Students From Low-income Families In Malaysia - Nurshahira Ibrahim; Tugba Erhan; Nur Izzaty Mohamad; Faridah Che Husain; Ramlan Mustapha; Tengku Maaidah Tengku A. Razak; Umi Hamidaton Mohd Soffian Lee (International Journal of Religion, 2024)
International Journal of Religion, Volume 5 Issue 1 Page (328-339)